2011
DOI: 10.1145/1978802.1978806
|View full text |Cite
|
Sign up to set email alerts
|

Forensic identification by computer-aided craniofacial superimposition

Abstract: Craniofacial superimposition is a forensic process in which a photograph of a missing person is compared with a skull found to determine its identity. After one century of development, craniofacial superimposition has become an interdisciplinary research field where computer sciences have acquired a key role as a complement of forensic sciences. Moreover, the availability of new digital equipment (such as computers and 3D scanners) has resulted in a significant advance in the applicability of this forensic ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 76 publications
0
26
0
1
Order By: Relevance
“…The isolation of the decision making stage given a SFO While the negative influence of the first five issues outlined above is quite evident, the sixth is not clear at all. In contrast to recent computerized approaches that clearly differentiates between SFO and Decision making stages [8,9,10], the process of overlaying the skull over the face traditionally [2,11,25] involved a continuous comparison of the skull-face relationship. While, this task is avoided in the present study since the participants directly received the SFO, the approach followed guarantees a more objective framework where all the participants examine the list of criteria using the same SFO (that are objective and accurate in the case of positive cases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation of the decision making stage given a SFO While the negative influence of the first five issues outlined above is quite evident, the sixth is not clear at all. In contrast to recent computerized approaches that clearly differentiates between SFO and Decision making stages [8,9,10], the process of overlaying the skull over the face traditionally [2,11,25] involved a continuous comparison of the skull-face relationship. While, this task is avoided in the present study since the participants directly received the SFO, the approach followed guarantees a more objective framework where all the participants examine the list of criteria using the same SFO (that are objective and accurate in the case of positive cases).…”
Section: Discussionmentioning
confidence: 99%
“…Although the foundations of the CFS method were laid by the end of the nineteenth century [5,6], the associated procedures evolved as new technologies became available. As a result, distinct approaches have developed: photographic, video, and computer-aided superimposition [1,7,8]. Regardless of the applied technology, some authors have recently described three different stages for the whole CFS process [8,9]: i) the acquisition and processing of the skull (or skull 3D model) and the ante mortem facial images together with the anatomical landmarks; ii) the skull-face overlay (SFO), which focuses on achieving the best possible superimposition of the skull and a single ante mortem image of the missing person.…”
Section: Introductionmentioning
confidence: 99%
“…The whole CFS process can be divided into three consecutive stages [3], [4]: 1) The acquisition and processing of the materials, i.e, skull and ante-morten (AM) facial images, and the location of somatometric landmarks on both; 2) skull-face overlay (SFO), which deals with accomplishing the best possible superimposition of the skull and a single AM photograph of a missing person. This procedure is iteratively executed for each photograph, thus obtaining different overlays; and 3) decision making, which aims to determine the degree of support for a match based on the SFOs achieved in the previous step.…”
Section: Introductionmentioning
confidence: 99%
“…They differentiate three additional categories within the latter family of methods: computer-aided craniofacial photo superimposition, computer-aided craniofacial video superimposition, and computer-aided craniofacial 3D-2D superimposition. In addition, to properly characterize any CFS system, Damas et al [15] identified and defined different stages involved in the process: face enhancement and skull modelling (FESM), skull-face overlay (SFO), and decision making (DM). The first stage involves achieving a digital model of the skull and the enhancement of the image of the face.…”
Section: Introductionmentioning
confidence: 99%